Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu dalam Pertolongan Pertama Kejang Demam - Sahensolar, Donny; Susiawati, Ni Wayan Medi Seri (Yayasan Syalom Cipta Sumikolah, 2025)
Children are the jewel or hope of the family. Everyone has obligations and responsibilities towards their children to grow up healthy. However, during childhood, children are often susceptible to infection, because children are often affected by various diseases, one of which is febrile seizures. Febrile seizures are the most common neurological disorder in children. The impact of febrile seizures if left untreated will damage brain cells due to lack of oxygen in the brain, excess secretions and the risk of emergencies for airway aspiration which causes airway obstruction, if not treated properly there is a risk of death, but when a child has a seizure, the mother often experiences confusion in dealing with febrile seizures due to lack of knowledge. The purpose of this study was to determine the Effect of Health Education on Mothers' Knowledge in First Aid for Febrile Seizures in the Edelweys Room, Bhayangkara Hospital, Level III, Manado. The research design used the Quasi Experiment method with a one-group pre-post test design. The population in this study was 50 mothers. The number of samples in the study was 16 respondents. The data analysis used was univariate and bivariate analysis with the T-Test test. The results of this study indicate that before being given health education, the mother's knowledge was mostly sufficient knowledge, there were 11 respondents (68.8%), and after being given health education, there was an increase in mothers with good knowledge, there were 13 respondents (81.2%), the bivariate results of the samples studied showed the Effect of Health Education on Mothers' Knowledge in First Aid for Febrile Seizures in the Edelweys Room of Bhayangkara Hospital Level III Manado with a value of ρ = 0.000 <α = 0.05. There is an Effect of Health Education on Mothers' Knowledge in First Aid for Febrile Seizures in the Edelweys Room of Bhayangkara Hospital Level III Manado. These results are expected to be input for research locations regarding the importance of mothers' knowledge in providing first aid to children experiencing febrile seizures.